PEMASARAN KACANG TANAH DI DISTRIK BUGI KABUPATEN JAYAWIJAYA - Ilanus ., Medlama; Benny Adrian Berthy Sagay; Yolanda Pinky Ivanna Rori (AGRI-SOSIOEKONOMI, 2019)
The purpose of this study was to describe the marketing of peanuts in Bugi District, Jayawijaya Regency. The study was conducted from January to March 2019. Data and information were collected from primary sources and secondary sources. The selection of respondents was done purposevely. Primary data was collected from interviews with 20 farmers who are farmers as well as sellers of peanuts based on a list of questions that had been prepared and direct observations on marketing activities of peanuts at the study site. Secondary data was collected from the Bugi District office, Statistics report of Jayawijaya Regency Central Bureau, the internet through google search and google scholar to obtain journal article and thesis those related to the topic of peanut marketing. The analysis used is a qualitative analysis method. The results of the study show that farmers are easier to obtain market information about prices and act as determinants of prices because farmers sell directly to the market by bringing their own produce so that it does not require costs to obtain price information on the market.-*eprm*